Phytohormone Profiling Method for Rice: Effects of GA20ox Mutation on the Gibberellin Content of Japonica Rice Varieties - López-Cristoffanini, Camilo; Serrat, Xavier; Jáuregui, Olga; Nogués, Salvador; López-Carbonell, Marta (Frontiers in Plant Science, 2019)
Gibberellins (GAs) are a very important group of phytohormones involved in seed germination, vegetative growth, flowering, and fruit development, being only 4 of the 136 known bioactives: GA1, GA3, GA4 and GA7. It has been evidenced that mutations in the OsGA20ox-2 gene produce rice (Oryza sativa) dwarf varieties, which were one of the main pillars of the green revolution. In this work two main objectives were proposed: (i) develop a rapid and broad phytohormone profiling method and (ii) to study the effects on the GA content of the GA20ox-2 mutation in several rice developmental stages using three varieties (tall variety, elite variety, mutated variety). A phytohormone extraction using an SPE step and HPLC-MS/MS detection using a QqQ instrument was determined which resulted in limits of detection (LOD) and limits of quantification (LOQ) for GAs that varied between 0.1-0.7 and 0.3-2.3 pg·g-1 (f.w.) of rice sample respectively, allowing highly sensitive phytohormones detection in samples. Moreover, a good reproducibility was obtained for the GAs as relative standard deviations (RSD) for a 40 ng·mL-1 pattern varied between 0.3-0.9%. Notoriously, GA1 was absent in the coleoptile and GA4 was the GA with higher content in the majority of developmental stages. We also observed a large content increase of the 4 bioactive GAs in the internode of the flag leaf of the mutated variety allowing to reach same height as the elite variety. Therefore, we provide a rapid and broad phytohormonal profiling method and evidence that the GA20ox-2 mutation is not the only factor generating dwarf varieties. To our knowledge, this is the first study that it has been reported such a high number of analyzed gibberellins at the same time in rice (Oryza sativa ssp. japonica).